A Nurse-Led Implementation Science Specialist Program. - Russell-Babin, Kathleen; Friesen, Mary Ann; O'Brien, Anne-Marie; McLaughlin, Maureen Kirkpatrick; Messing, Jonathan; Mowery, Bernice; Bettencourt, Amanda P.; Graling, Paula R. (AJN American Journal of Nursing, 2023)
A well-known challenge in health care is integrating evidence into practice. Implementation science (IS) is a growing field that promotes the sustainable application of evidence-based practice (EBP) to clinical care. Health care organizations have an opportunity to support sustainable change by creating robust IS infrastructures that engage nurses in the clinical environment. Integrating IS into a nursing shared governance model is an ideal vehicle to empower direct care nurses to sustain EBP. Importantly, an IS infrastructure may also promote nurse retention and increase interdisciplinary collaboration. This article, the first in a series on applying IS, describes how a multisite health care organization developed a systemwide nurse-led IS Specialist program within a shared governance model. This article, the first in a series, describes how a multisite health care organization developed a systemwide nurse-led Implementation Science Specialist program within a shared governance model.